Implementation of a Faraday rotation diagnostic at the OMEGA laser facility - Rigby, A; Bott, A; White, T; Tzeferacos, P; Lamb, D; Froula, D; Gregori, G (Cambridge University Press, 2018)
Magnetic field measurements in turbulent plasmas are often difficult to perform. Here we show that for ⩾ kG magnetic fields, a time-resolved Faraday rotation measurement can be made at the OMEGA laser facility. This diagnostic has been implemented using the Thomson scattering probe beam and the resultant path-integrated magnetic field has been compared with that of proton radiography. Accurate measurement of magnetic fields is essential for satisfying the scientific goals of many current laser–plasma experiments.